Non-compliance with Constitutional Court Decisions as an Act of Contempt of Court: Ketidakpatuhan Terhadap Putusan Mahkamah Konstitusi Sebagai Suatu Perbuatan Contempt of Court - Freidelino de Sousa (Universitas Negeri Semarang, 2022)
As one of the institution that holding the judicial power according to article 24 and 24C in Constitution of Republic of Indonesia, Constitucional Court is enforcing the law and justice through its decisions. By Its decisions, the expectation is all the legal issues in constitucional field could be resolved. Disobeying of Constitucional Courts orders is categorized as contempt of Constitucional Court as judicative branch. Disobeying of constitucional courts order principally is a contempt of court, where it could be punished according to article 216 (1) Indonesian Penal Code.